Risk factors for post-COVID-19 condition (Long Covid) in children: a prospective cohort study - Morello, R; Mariani, F; Mastrantoni, L; De Rose, C; Zampino, G; Munblit, D; Sigfrid, L; Valentini, P; Buonsenso, D (Elsevier, 2023)
Background Adults and children can develop post-Covid-19 condition (PCC) (also referred to as Long Covid). However, existing evidence is scarce, partly due to a lack of a standardised case definition, short follow up duration, and heterogenous study designs, resulting in wide variation of reported outcomes. The primary aim of this study was to characterise risk factors for PCC and longitudinal rates of recovery in a cohort of children and young people using a standardised protocol.